AI for Inclusive and Accessible Education = الذكاء الاصطناعي لدعم التعليم للجميع - Mohamed Koutheair Khribi (18526731) (2024)
تستكشف الورشة التدريبية الإمكانيات التحولية الهائلة للذكاء الاصطناعي في تعزيز التعليم الشامل وسهل الوصول للجميع. سيتعرف المشاركون في هذه الورشة إلى مجالات تقاطع الذكاء الاصطناعي والتعليم، حيث سيتم التذكير بأساسيات الذكاء الاصطناعي واستخداماته وكيفية الاستفادة منه لتعزيز الشمول والوصول إلى فرص التعليم للجميع. كما تقدم الورشة نظرة عامة على الذكاء الاصطناعي في التعليم من جوانب مختلفة بما في ذلك السياسات، والكفاءات، والتطبيقات، والأدوات، والممارسات، نحو ضمان بيئة تعلم شاملة للجميع بالاستفادة من الإمكانات الكامنة في الذكاء الاصطناعي. This open educational resources workshop explores the transformative potential of Artificial Intelligence (AI) in promoting inclusive and accessible education. Learners will be introduced into the intersection of AI and education exploring the fundamentals of AI and its applications in the educational context, in particular, how it can be leveraged to enhance inclusivity and accessibility in education. The resource will provide an overview of AI in education from different aspects including policies, competencies, applications, tools, and practices, toward creating an inclusive learning environment for all harnessing AI. Other Information Published in: Mada Academy License: https://creativecommons.org/licenses/by-nc-sa/4.0/ See educational resource on Mada Academy: <a href="https://cdn.academy.mada.org.qa/data/wp-content/uploads/2024/06/الذكاء-الاصطناعي-لدعم-التعليم-للجميع.pdf?_gl=1*17027yt*_ga*Mzk1Njc4MjQxLjE2NzM3NjE3MDk.*_ga_TMT1BE97W2*MTcxODA5Njk4OC4xNTkuMS4xNzE4MDk4MTA3LjAuMC4w" rel="noreferrer" target="_blank">https://cdn.academy.mada.org.qa/data/wp-content/uploads/2024/06/الذكاء-الاصطناعي-لدعم-التعليم-للجميع.pdf?_gl=1*17027yt*_ga*Mzk1Njc4MjQxLjE2NzM3NjE3MDk.*_ga_TMT1BE97W2*MTcxODA5Njk4OC4xNTkuMS4xNzE4MDk4MTA3LjAuMC4w